Assessment Of Knowledge & Skills of Staff Involved in Providing Routine New-Born Care at Various Public Health Facilities of Rajkot District - Kaushik K Lodhiya; Dipesh D Zalavadiya; Chintan K Dashratha; Ankit P Viramgami; Ashutiosh D Jogia; Amiruddin M Kadri (Medsci Publications, 2016)
Background: The first hour after birth have a major influence on the survival, future health and well being of a newly born infant. The care health care providers give during this period is critical in ensuring infant survival. Aim: to evaluate the knowledge and skills of health care providers, regarding routine newborn care. Methods: It was a cross sectional observational study conducted during August 2013 to October 2013 at 36 Government health facilities of Rajkot district. Study participants were doctors and nursing staff working at different level of Newborn care facilities. Pre-tested semi-structured questionnaire was used for data collection. Their skills were assessed by simulation on a mannequin. Results: Less than one third of the staff knew all the signs of attachment for breast feeding. It was noted that the staff members trained in New-born care (NBC) services demonstrated better skills for neonatal resuscitation, prevention of hypothermia, breast feeding skills, etc than those untrained in the same. There was positive co-relation between duration of work experience and skills score. Conclusions: The knowledge and skills of health staff in routine NBC was not satisfactory. Experienced and staff trained in routine New born care services, had higher skills for the same.